Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I understand how to prove the scaling property of Fourier Transforms, except the use of the absolute value:

If I transform $f(at)$ then I get $F\{f(at)\}(w) = \int f(at) e^{-jwt} dt$ where I can substitute $u = at$ and thus $du = a dt$ (and $\frac{du}{a} = dt$) which gives me:

$ \int f(u) e^{-j\frac{w}{a}u} \frac{du}{a} = \frac{1}{a} \int f(u) e^{-j\frac{w}{a}u} du = \frac{1}{a} F \{f(u)\}(\frac{w}{a}) $

But, according to various references, it should be $ \frac{1}{|a|} F \{f(u)\}(\frac{w}{a}) $ and I don't understand WHY or HOW I get/need the absolute value here?

share|cite|improve this question
up vote 5 down vote accepted

First, lets convince ourselves that $F\{f(-t)\}(\omega)=F\{f(t)\}(-\omega)$:

$$ F\{f(-t)\}(\omega)=\int_{t=-\infty}^{t=\infty} f(-t)e^{-j\omega t}dt\quad\star $$ Set $u=-t$, so $dt=-du$. Also note that when $t=-\infty,$ $u=\infty$ and when $t=\infty$, $u=-\infty$. So,
$$ \star=-\int_{u=\infty}^{u=-\infty}f(u)e^{j\omega u}du\quad \star\star $$ recall that $$ -\int_{a}^bf(x)dx=\int_b^af(x)dx $$ which explains the flipping of the integration bounds. Hence $$ \star\star=\int_{u=-\infty}^{u=\infty}f(u)e^{j\omega u}du $$ which is exactly $F\{f(t)\}(-\omega)$

Then, if $a<0$ we can simply write $a=-\vert a\vert$, so that $F\{f(at)\}=F\{f(-\vert a\vert t)\}(\omega)=F\{f(\vert a\vert t)\}(-\omega)=\frac{1}{\vert a\vert}F\{f(t)\}(\frac{-\omega}{\vert a\vert})=\frac{1}{\vert a\vert}F\{f(t)\}(\frac{\omega}{a})$

share|cite|improve this answer
Ok, I'm trying to understand how to get rid of the - at the time reversal case. When they ( substitute t by -t' they also swap the borders of the integral (because of dt = -dt'; which is what I do not understand correctly). And when they swap them back they have to add another - (I understand why, this is a simple rule with integrals). Those two - then eliminate each other ... but why do they swap the borders in the first place? – Daniel Jour Dec 17 '12 at 0:27
See edits - it's standard integration stuff from "calc II", but its easy to get lost in the negative signs. – icurays1 Dec 17 '12 at 0:42
"when t=∞ u=−∞." THAT was the part I missed/didn't think of. Thank you, that solves my problem! :) – Daniel Jour Dec 17 '12 at 3:53

Think about the range of the variable $t$ in the integral that gives the transform. How do the 'endpoints' of this improper integral transform under $t\to at$? Can you see how this depends on the sign of $a$?

share|cite|improve this answer
Hm .. I'm not sure whether I got it: If $a$ is negative, then I would "change" the "direction" of the integral which is equivalent to exchanging the 'endpoints' ... hm, no, I don't think I got it. Is it possible to ... well .. use a equation that is explaining this problem? – Daniel Jour Dec 16 '12 at 23:11

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.